SEASONAL VARIATIONS IN NATURAL PROCESSES AND ATMOSPHERIC PRECIPITATION - Descherevsky A.V.; Sidorin A.Ya. (My University, 2004)
To study the nature of seasonal variations in time series measured at the Garm test site, a local model based on the experimental data of atmospheric precipitation penetration into the soil has been proposed. It is intended for filtration of exogenous variations in the data of various time series and a study of statistical structure of different natural processes, including earthquake preparation processes, and the mechanisms of their effect on the biosphere. Using this model, we analyze and compare variations in apparent resistivity and properties of rock moistening. It has been shown that at small current-electrode (AB) separations among all the parameters of water regime, only water saturation of the active soil layer reveals a significant correlation with apparent resistivity variations. When increasing the current-electrode separation, the seasonal variation form varies from quasi-sinusoidal in the upper layer up to quasi-triangular at the largest investigated depths (maximum separations).